PERSEPSI MASYARAKAT TENTANG BANK SYARI’AH: Studi Kasus Di Kelurahan Jatijajar, Tapos, Depok Jawa Barat - Administrator, Journal (Al Mashalih - Journal of Islamic Law, 2018)
This study aims to determine how much knowledge in Jatijajar urban village about syari'ah banks from teachers, students to housewives. In this study the authors used interviews and questionnaires that distributed to 20 respondents, which are classified from various professions such as: teachers, housewives, village cadres, students. Collected data is primary and respondents datas that collected by interviews and distribute questionnaire in the form of notes and documents. The researcher finds the factors that influence the public perception of the Sharia Bank, including: (1) the circumstances surrounding the person and the information he or she receives from time to time, (2) the level of prior knowledge and experience that he possesses, and (3) the ability sense and feelings in describing things.